THE SYSTEM APPROACH TO MEASURING CHANNEL MODELLING AS THE MECHANISM OF MAINTENANCE OF TRUST TO RESULTS OF MEASUREMENTS - P. S. Serenkov; E. N. Savkova (Приборы и методы измерений, 2015)
Necessity of system approach development to measurement modeling for the purpose of maintenance of the trust set level to their results is proved. The decision of a measuring problem subject to determined aim is considered as creation of models sequence: measurement process model and complex measuring channel model. As a demonstrative basis of maintenance of trust to result of measurements the complex of criteria of completeness and irredundant is formulated.